A profile of professional nursing practice in the private sector in the R.S.A. - S. Pera (AOSIS, 1988)
The purpose of this study was to develop a profile of professional nursing practice in private enterprise health care services in the Republic of South Africa. In the light of the future health care needs and the relationship between the private and public sector health care establishments, information about the role and task of the I professional nurse was needed. Information would provide a data base about the registered nurse and so facilitate future health care planning. An exploratory field study was undertaken to locate the various work environments of the registered nurse in four statistical urban regions. Questionnaires were handed out and collected from a proportional stratified sample of professional nurses who were working in thirteen types of health care environments in the period between I June 1983 and 30 September 1983. A return rate of 68 percent yielded 340 completed questionnaires from 501 registered nurses. The study revealed that the majority of nurses in the private sector were relatively young. White, female, English-speaking professionals who were practising in four broad areas of health care: • Custodial care environments such as residential homes for the aged, institutions for the chronic sick and frail aged, homes for children and homes for the adult handicapped. • Hospitals and related special health centres catering for drug addicts, alcoholics and patients suffering from psychiatric/nervous disorders. • Institutions for child and adult education which included crèches/nursery schools, primary and secondary hoarding schools, special schools for the handicapped, and university based student health centres. • Medical and dental consulting room practices. • Other entrepreneurial employment settings such as business and industrial occupational health care services, nursing service agencies, and mobile emergency care units.